Химико-физические механизмы термической инактивации процессов экситонного дефектообразования и образования биомолекулярных нанокомплексов в радиационной технологии, биотехнологии и биофизике: спектроскопия и термодинамическое моделирование - Огурцов, Александр Николаевич; Близнюк, Ольга Николаевна; Клещев, Николай Федосович; Масалитина, Наталья Юрьевна (НТУ "ХПИ", 2013)
В рамках наближення Арреніуса-Ейрінга досліджено процеси термічної інактивації екситонних пасток екситонів в кріокристалах криптону та фермент-субстратних нанокомплексів. Визначено такі термодинамічні параметри цих процесів, як енергія активації, ентальпія і ентропія інактивації.

Within the framework Arrhenius-Eyring approach the thermal inactivation processes of excitonic traps in krypton cryocrystals and enzyme-substrate nanocomplexes were studied. Such thermodynamics parameters of these processes as activation energy, enthalpy and entropy of inactivation were determined.
Chemical-physics mechanisms of thermal inactivation of the processes of excitonic defect formation and biomolecular nanocomplexes formation in radiation technology, biotechnology and biophysics: spectroscopy and thermodynamical modeling
Keywords: химические процессы; химическая кинетика; термоактивация; инактивация; температурная инактивация; дефектообразования; криокристаллы